Cytotoxicity and apoptosis activities of passion fruit (Passiflora edulis Sims) seed extract on HSC-2, HSC-3, MCF-7, and HaCaT cell lines - Liza Meutia Sari; Dina Keumala Sari; Arleni Bustami; Achmad Danny Gazali; Elza Ibrahim Auerkari (GarVal Editorial Ltda., 2024)
Context: Passion fruit (Passiflora edulis Sims) is a well-known plant in the tropical islands, especially in North Sumatra, Indonesia, because of its sweet and refreshing taste. Although the fruit is often used as a syrup and sweetener, the efficacy of P. edulis fruit seed extract for anticancer activity has not been widely studied. Aims: To evaluate the ability of P. edulis fruit seed extract to induce cytotoxicity and apoptosis in HSC-2, HSC-3, MCF-7, and HaCaT cell lines. Methods: P. edulis fruit seed extract was extracted by using 96% ethanol. The cytotoxicity activity was measured by using an MTT assay for 48 hours. Apoptosis was examined using a TUNEL assay, and the morphology of the apoptosis bodies was analyzed using electron microscopy. Results: The IC50 values of P. edulis fruit seed extract were 572.79 µg/mL and 439.54 µg/mL for HSC-3 and MCF-7, respectively. The seed did not show cytotoxic activity on the HSC-2 cell line, but it induced proliferation of the HaCaT cell line in the maximum dose. The P. edulis fruit seed extract induced apoptosis activity in HSC-3, MCF-7, and HaCaT cell lines. Most DNA fragments were found in the cytosol of HSC-3 cells and the nucleus of MCF-7 cells. Conclusions: The P. edulis fruit seed extract has cytotoxicity and apoptosis activities in oral cancer (HSC-3 cells) and breast cancer (MCF-7 cells), as well as being safe in normal human keratinocytes (HaCaT cell line). The P. edulis fruit seed extract can be considered an adjuvant agent in cancer treatment.